Beliefs and Determinants of Use of Traditional Complementary/Alternative Medicine in Pediatric Patients Who Undergo Treatment for Cancer in South America - Rocha, Valeria (2017)
Purpose The use of traditional complementary/alternative medicine (TCAM) among children with cancer has been well documented. South America has a rich history of traditional healers and medicinal resources; however, little is known about the use of TCAM among children with cancer. We sought to investigate patterns, beliefs, and determinants of TCAM use among South American children with cancer. Methods A cross-sectional survey was administered to 199 children treated for cancer at institutions located in Buenos Aires, Argentina, and Montevideo, Uruguay. Participants were queried about the type of TCAM and strength of beliefs associated with its use. Logistic regression analysis was used to estimate the odds ratios with 95% CIs. Results We found that the use of TCAM was common in both Argentina (47%) and Uruguay (76%). Variations in the forms of TCAM used were observed between the countries; however, both countries used TCAM primarily for supportive care. Mother's education, wealth index, and TCAM belief system were significant predictors of TCAM. Conclusion To our knowledge, this study is the first to report on the use of TCAM in pediatric oncology in South America. The study identifies several predictors of TCAM use, which may serve as target variables for educational and research initiatives. The finding that most families use TCAM for supportive care suggests that future efforts could evaluate the role of TCAM to enhance existing supportive care regimens, particularly in settings where access to conventional medications are limited.